Mutu Tenaga Kerja Dan Pengawasan Tenaga Kerja - Ria Sari Ayu (Jurnal Transformasi Bisnis Digital, 2024)
The quality of labor and supervision of labor is an important aspect in the success of an organization or company. Good workforce quality greatly influences the productivity, efficiency and overall performance of the organization. On the other hand, labor inspection plays a key role in ensuring that workers carry out their duties according to established standards, as well as ensuring compliance with existing policies and procedures. This research aims to analyze the relationship between labor quality and labor supervision in the context of a modern work environment. The research method used involves a comprehensive literature review to explore concepts, theories and practices related to these two aspects. The results of the analysis show that there is a close relationship between labor quality and labor supervision, where effective supervision can improve labor quality and vice versa. The implication of this research is that it is important for companies to develop effective monitoring strategies to ensure optimal workforce quality, which in turn will contribute to achieving overall organizational goals.